Antihypoxic Activity of Native Humic Acids of Tomsk Lowland Peat; Pharmaceutical Chemistry Journal; Vol. 48, iss. 2 - Belousov M. V. Mikhail Valerievich; Akhmedzhanov R. R. Rafik Raviljevich; Zykova M. V. Mariya Vladimirovna; Arbuzov A. N.; Gurjev A. M. Artyom Mikhaylovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2014, 2014)
Title screen